A Unifying Theory of Evolution Generated by Means of Information Modelling - Jytte Brender McNair (Studies in Health Technology and Informatics, 2016)
"Stringent ways of thinking, 'conceptual frameworks', are necessary in science. The drawback is that the associated assumptions, concepts, rules and practice may become so deeply entrenched that they turn into tacit knowledge and hence give rise to constraints in scientific thought and practice - that is, a new kind of plethora that seriously blinds and thereby hampers scientific progress. This book, 'A Unifying Theory of Evolution Generated by Means of Information Modelling', presents a methodology for describing complex knowledge domains. It applies a template information model based on a dynamic structure of interrelated functions, called the Mereon Matrix. Application of this template model to the field of evolutionary theories enabled the unification of the sometimes chaotic and competing field of evolutionary theories, large and small, seamlessly in a shared framework. The author has Masters degrees in both biochemistry and computer science, as well as a European Doctorate and PhD in health informatics and has spent 35 years in full-time research. It is her particular combination of professional experience and expertise together with the template information model which has enabled her to write this book. Whilst primarily aimed at a scientific audience, and evolutionary biologists in particular, the book will be of interest to all those looking for new approaches to exploring and explaining phenomena in nature, and because the text is largely non-technical in nature, much of the content will also be accessible to a wider readership."